PEMBUATAN EMBEDING/BIOPLASTIK HEWAN INVERTEBRATA DI BAKAL SEKOLAH ALAM “ISYO HILLS” KAMPUNG WISATA RHEPANG MUAIF NIMBOKRANG, KABUPATEN JAYAPURA - Evie Lilly Warikar; Euniche R.P.F. Ramandey (JURNAL PENGABDIAN PAPUA, 2022)
The high biodiversity in Papua can be used as biology learning material and an educational laboratory model for students in Repang Muaif Village. The diversity of animals, plants and microorganisms can be introduced or shown easily in the classroom to students with a learning medium. Facts in the field show that most teachers still provide biology material verbally without adequate media or teaching aids. This kind of learning model will inhibit the development of reasoning, interest and motivation of children to learn biology. Most biology teachers carry out learning without props because they do not have much time to provide it or do not have adequate tools / materials in school. Teachers at the nature school in the Rhepang Muaif should be able to take advantage of the existence of invertebrates in the forest around the school as learning media or teaching aids for their students. One effort that can be made to develop instructional media in schools is to introduced a technique for making invertebrate bioplastics/embedding. The purpose of this training was to introduce and practice directly the collection techniques and to introduced a technique for making invertebrate bioplastics/embedding to participants in Rhepang Muaif. This training was held on 7-9 September 2020 in Rephang Muaif Village, Nimbokrang, Jayapura-Papua. The target audience involved in this activity are young people who will become prospective teaching staff at this natural school. They come from the Rhepang Muaif and from several communities in Jayapura. The training was held for 3 days, involving 53 participants. The material provided was a technique of collecting invertebrate animals in the environment around the house yards, forests and gardens in Rhepang Muaif Village. Furthermore, making invertebrates bioplastic/embedding media obtained from the field by following the existing procedures to produce bioplastic/embedding media. The training which was conducted for the teaching staff and management of the Nature School in Rephang Muaif Village has been going well. The enthusiasm of the participants in participating in this training was very high. This indicates that the training participants have responded positively to the activities that have been carried out. Keywords: :  Training, Embedding/Bioplastics, Invertebrate Animals, Rephang Muaif